Transmembrane protein 64 modulates prostate tumor progression by regulating Wnt3a secretion - Moon, Yeon Hee (Oncol Lett, 2019)
Wnt3a is a glycosylated ligand that activates the β-catenin-dependent signaling pathway. Wnt signaling is also important in the prostate tumor microenvironment, and Wnt proteins secreted by the tumor stroma promote resistance to therapy. Bioactive Wnt3a production requires a number of dedicated factors in the secretory cell, but their coordinated functions are not fully understood. We previously reported transmembrane protein 64 (Tmem64) as a novel regulator of the Wnt/β-catenin signaling pathway, which is correlated with β-catenin regulation. In the present study, the role of Tmem64 in prostate cancer cells was investigated by modulating Wnt3a secretion. Overexpression of Tmem64 inhibited Wnt3a secretion and Lef/Tcf-sensitive transcription. By contrast, a Tmem64 mutation deleting the protein's transmembrane region restored Wnt3a secretion. Notably, Tmem64 protein and mRNA in PC3 cells were significantly overexpressed compared with that observed in LNCaP and DU145 cells. In a mouse metastasis model intracardially injected with PC3 cells, Tmem64 expression was downregulated in the metastatic spine and mandible lesions compared with in the primary injection regions. However, Wnt3a was strongly expressed in the metastatic spine and mandible lesions. Collectively, these findings suggest that Tmem64 is involved in the metastatic progression of prostate cancer cells by regulating Wnt3a secretion.